Adopting search-based algorithms for pairwise testing - Abdullah, Nasser; Alsewari, Abdulrahman A.; Kamal Z., Zamli (IEEE, 2015)
Owingto an exponential increase in computational time associated with increasing number of components, exhaustive testing is impractical. Here, many researchers opt to adopt pairwise testing to minimize the overall number of tests. Recently, many existing work are focusing on the use of SearchBased algorithms as the basis of the implementation algorithm. This paper presents a critical comparison of Search-Based algorithm for generating the pairwise test suite. An analysis of existing SB pairwise strategies shows the positive and negative points for each strategy thereby highlighting promising future directions in this area.